(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The consumption of nutraceuticals has become progressively popular in improving health, as well as disease treatment and prevention. The aim of this study is to evaluate the ameliorative effect of fermented Pentaclethra macrophylla (African oil bean) seed on high fat diet and sucrose drink induced metabolic syndrome in male New Zealand rabbits. All experimental procedures were carried using standard methods. A total of twenty (20) rabbits were used for this study, the animals were randomly grouped into five (5) groups with four (4) animals each. Metabolic syndrome risk factors obesity, hypertension, dyslipidemia and hyperglycemia were determined. HFD+30%SUC had over 1500g body weight (bwt) and fasting blood sugar (FBS) 239.50±5.74 mg/dl relative to the normal control with 1000±6.73g and 77.00±5.94 respectively whereas ND+30%SUC had lower FBS (l172.50±2.52) compared to HFD+30%SUC. There was a significant p<0.05 increase in body weights in treated groups with 1274±11.19g, 1282.75±4.99g, 1285±4.76g and FBS levels in mg/dL198.25±4.79, 198.75±8.06, 200±3.74 in rabbits compared to untreated HFD+30%SUC. Glycated hemoglobin, and α-Amylase were significantly p<0.05 elevated, glucose-6-phosphate dehydrogenase levels were significantly p<0.05 reduced, lipid profile markers (HDL, TRIG & CHOL), electrolytes (sodium, potassium, calcium), urea and creatinine levels were significantly p<0.05 altered in HFD+30%SUC exposed group relative to the normal control and ND+30%SUC. However, dietary supplementation with fermented Pentaclethra macrophylla seeds caused weight, FBS, serum lipid reduction and potentiated electrolyte, urea and creatinine levels. Therefore, according to our results, fermented Pentaclethra macrophylla seed is an excellent nutraceutical and its consumption should be encouraged in modifying high fat and elevated intake of sucrose in rabbit